Gen Z’s Business Preferences: Identifying The Innovative Learning on Entrepreneurial Classroom - Dwi Hasmidyani; Ikbal Barlian; Siti Fatimah; Muhammad Akbar Budiman (Program Studi Pendidikan Ekonomi FKIP Universitas Lambung Mangkurat, 2026)
The digital era has significantly transformed business practices and educational approaches. This study aims to identify Gen Z’s business preferences based on their characteristics and examine differences between male and female students to inform entrepreneurship learning. A mixed-method approach with a concurrent nested design was employed, where qualitative data served as the primary source and quantitative data provided complementary analysis.The findings show that Gen Z tends to prefer digital promotional media, non-seasonal products, and customizable offerings, while demonstrating balanced preferences between self-production and reseller models. They also show a stronger tendency toward individual entrepreneurship rather than collaboration. Their motivations include financial, personal, and social aspects, and they evaluate business success based on financial performance, customer relationships, innovation, and growth. Statistical analysis indicates no significant gender differences in business preferences.These findings suggest the importance of designing entrepreneurship learning that accommodates diverse preferences and emphasizes flexibility, innovation, and practical skills aligned with Gen Z characteristics. However, the study is limited to students majoring in economics education, necessitating caution in generalizing the results.